Influence of the Absolute Configuration of NPE‐Caged Cytosine on DNA Single Base Pair Stability1. (11th December 2013) - Steinert, Hannah S.; Schäfer, Florian; Jonker, Hendrik R. A.; Heckel, Alexander; Schwalbe, Harald
Abstract Photolabile protecting groups are a versatile tool to trigger reactions by light irradiation. In this study, we have investigated the influence of the absolute configuration of the 1‐(2‐nitrophenyl)ethyl (NPE) cage group on a 15‐base‐pair duplex DNA. Using UV melting, we determined the global stability of the unmodified and the selectively (S)‐ and (R)‐NPE‐modified DNA sequences, respectively. We observe a differently destabilizing effect for the two NPE stereoisomers on the global stability. Analysis of the temperature dependence of imino proton exchange rates measured by NMR spectroscopy reveals that this effect can be attributed to decreased base pair stabilities of the caged and the 3′‐neighbouring base pair, respectively. Furthermore, our NMR based structural models of the modified duplexes provide a structural basis for the distinct effect of the (S)‐ and the (R)‐NPE group.